MITOS JARI-JARI PEREMPUAN (KAJIAN GENDER DAN PERSPEKTIF AL-QUR’AN) - Karyanto, Umum B. (RELIGIA, 2009)
“Female’s fingers myth” is so believed by most female communities, especially Javanese ones. Fingers owned by them are described as their faithful with their husband. This belief is so strong that it impacts the violent action to them in most communities. This violence happens to both engage and married women. This phenomenon is often missed and hardly touched by law. It is because the violence happens to them is an oldest violence form, that most people view it as something common and proper. It is one of the supporting factors that the male’s superiority to female is imperishable. This perspective must be taken apart and reform soon in order that the gender bias does not happen, because the holy Qur’an as the Muslim’s guidance also does not teach that.